The Full Wiki

Trigonometric substitution: Wikis


Note: Many of our articles have direct quotes from sources you can cite, within the Wikipedia article! This article doesn't yet, but we're working on it! See more info or our list of citable articles.


From Wikipedia, the free encyclopedia

Topics in Calculus
Fundamental theorem
Limits of functions
Mean value theorem

In mathematics, trigonometric substitution is the substitution of trigonometric functions for other expressions. One may use the trigonometric identities to simplify certain integrals containing radical expressions:

  • If the integrand contains a2 − x2, let
x = a \sin \theta\,
and use the identity
1-\sin^2 \theta = \cos^2 \theta.\,
  • If the integrand contains a2 + x2, let
x = a \tan \theta\,
and use the identity
1+\tan^2 \theta = \sec^2 \theta.\,
  • If the integrand contains x2 − a2, let
x = a \sec \theta\,
and use the identity
\sec^2 \theta-1 = \tan^2 \theta.\,




Integrals containing a2x2

In the integral


we may use

x=a\sin(\theta),\quad dx=a\cos(\theta)\,d\theta, \quad \theta=\arcsin\left(\frac{x}{a}\right)

so that the integral becomes

 \begin{align} \int\frac{dx}{\sqrt{a^2-x^2}} & = \int\frac{a\cos(\theta)\,d\theta}{\sqrt{a^2-a^2\sin^2(\theta)}} = \int\frac{a\cos(\theta)\,d\theta}{\sqrt{a^2(1-\sin^2(\theta))}} \ & = \int\frac{a\cos(\theta)\,d\theta}{\sqrt{a^2\cos^2(\theta)}} = \int d\theta=\theta+C=\arcsin\left(\frac{x}{a}\right)+C \end{align}

Note that the above step requires that a > 0 and cos(θ) > 0; we can choose the a to be the positive square root of a2; and we impose the restriction on θ to be −π/2 < θ < π/2 by using the arcsin function.

For a definite integral, one must figure out how the bounds of integration change. For example, as x goes from 0 to a/2, then sin(θ) goes from 0 to 1/2, so θ goes from 0 to π/6. Then we have

\int_0^{a/2}\frac{dx}{\sqrt{a^2-x^2}} =\int_0^{\pi/6}d\theta=\frac{\pi}{6}.

Some care is needed when picking the bounds. The integration above requires that −π/2 < θ < π/2, so θ going from 0 to π/6 is the only choice. If we had missed this restriction, we might have picked θ to go from π to 5π/6, which would result in the negative of the result.

Integrals containing a2 + x2

In the integral


we may write

x=a\tan(\theta),\quad dx=a\sec^2(\theta)\,d\theta

so that the integral becomes

 \begin{align} & {} \qquad \int\frac{dx}{{a^2+x^2}} = \int\frac{a\sec^2(\theta)\,d\theta}{{a^2+a^2\tan^2(\theta)}} = \int\frac{a\sec^2(\theta)\,d\theta}{{a^2(1+\tan^2(\theta))}} \\[8pt] & {} = \int \frac{a\sec^2(\theta)\,d\theta}{{a^2\sec^2(\theta)}} = \int \frac{d\theta}{a} = \frac{\theta}{a}+C = \frac{1}{a} \arctan \left(\frac{x}{a}\right)+C \end{align}

(provided a ≠ 0).

Integrals containing x2a2

Integrals like

\int\frac{dx}{x^2 - a^2}

should be done by partial fractions rather than trigonometric substitutions. However, the integral

\int\sqrt{x^2 - a^2}\,dx

can be done by substitution:

x = a \sec(\theta),\quad dx = a \sec(\theta)\tan(\theta)\,d\theta
\theta = \arcsec\left(\frac{x}{a}\right)
 \begin{align} & {} \qquad \int\sqrt{x^2 - a^2}\,dx = \int\sqrt{a^2 \sec^2(\theta) - a^2} \cdot a \sec(\theta)\tan(\theta)\,d\theta \ & {} = \int\sqrt{a^2 (\sec^2(\theta) - 1)} \cdot a \sec(\theta)\tan(\theta)\,d\theta = \int\sqrt{a^2 \tan^2(\theta)} \cdot a \sec(\theta)\tan(\theta)\,d\theta \ & {} = \int a^2 \sec(\theta)\tan^2(\theta)\,d\theta = a^2 \int \sec(\theta)\ (\sec^2(\theta) - 1)\,d\theta \ & {} = a^2 \int (\sec^3(\theta) - \sec(\theta))\,d\theta. \end{align}

We can then solve this using the formula for the integral of secant cubed.

Substitutions that eliminate trigonometric functions

Substitution can be used to remove trigonometric functions. For instance,

\int f(\sin x,\cos x)\,dx=\int\frac1{\pm\sqrt{1-u^2}}f\left(u,\pm\sqrt{1-u^2}\right)\,du, \qquad \qquad u=\sin x
\int f(\sin x,\cos x)\,dx=\int\frac{-1}{\pm\sqrt{1-u^2}}f\left(\pm\sqrt{1-u^2},u\right)\,du \qquad \qquad u=\cos x

(but be careful with the signs)

\int f(\sin x,\cos x)\,dx=\int\frac2{1+u^2} f\left(\frac{2u}{1+u^2},\frac{1-u^2}{1+u^2}\right)\,du \qquad \qquad u=\tan\frac x2
\int\frac{\cos x}{(1+\cos x)^3}\,dx = \int\frac2{1+u^2}\frac{\frac{1-u^2}{1+u^2}}{\left(1+\frac{1-u^2}{1+u^2}\right)^3}\,du =
\frac{1}{4}\int(1-u^4)\,du = \frac{1}{4}\left(u-\frac15u^5\right) + C = \frac{(1+3\cos x+\cos^2x)\sin x}{5(1+\cos x)^3} + C

See also


Got something to say? Make a comment.
Your name
Your email address